PENGARUH PERENDAMAN DAGING PRA KYURING DALAM JUS DAUN SIRIH TERHADAP KETENGIKAN DAN SIFAT ORGANOLEPTIK DENDENG SAPI SELAMA PENYIMPANAN [The Effect of Soaking of Beef in Betle (Piper betle L) Leaf Juice Prior to Curing on Rancidity and Sensory Charact - Anang Mohamad Legowo; Soepardie ,; Rita Miranda; Indira Susi Nur Anisa; Yuli Rohidayah (Jurnal Teknologi dan Industri Pangan, 2002)
The research was carried  out to determine the effect of soaking of beef in betle (Piper betle L) leaf juice prior  to curing on peroxide level, thiobarbituric acid (TBA) score, and sensory characteristics of beef “dendeng” during 1-3 months storage. The result in showed that soaking in 10%  of betle leaf juice resulted in “dendeng” with peroxide level of 8.69 meq/kg which was significantly lower  than that of “dendeng” without soaking. TBA scores of “dendeng” soaked in 10% betle leaf juice after 1, 2, and 3 months storage were 0.0131, 0.0159, and 0.0168 μ mole MA/kg, respectively. These scores were lower than that of threshold score of food rancidity (18 μ mole MA/kg). Sensory characteristics (color, taste, and aroma) of “dendeng” during storage were accepted well by the panellists.